EGFR-TKI Plus Anti-Angiogenic Drugs in EGFR-Mutated Non–Small Cell Lung Cancer: A Meta-Analysis of Randomized Clinical Trials. Issue 6 (29th July 2020) - Conforti, Fabio; Pala, Laura; Bagnardi, Vincenzo; Specchia, Claudia; Oriecuia, Chiara; Marra, Antonio; Zagami, Paola; Morganti, Stefania; Tarantino, Paolo; Catania, Chiara; De Marinis, Filippo; Queirolo, Paola; et al.
Abstract: Background: Results of several randomized clinical trials (RCTs) testing the combination of an epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) plus an anti-angiogenic drug in advanced EGFR-mutated non–small cell lung cancer were reported. Methods: We first report a systematic review and meta-analysis of all RCTs to estimate effectiveness and toxicity of this new therapeutic approach compared with first-generation EGFR-TKI monotherapy. Subsequently, we present a network meta-analysis comparing the combination of an EGFR-TKI plus an anti-angiogenic drug with 2 new treatment options: combination of an EGFR-TKI plus chemotherapy or new EGFR-TKIs of second or third generation as monotherapy. Results: Five RCTs were included in the first meta-analysis. The progression-free survival (PFS) was statistically significantly larger in patients treated with an EGFR-TKI plus an anti-angiogenic drug compared with EGFR-TKI monotherapy: the pooled PFS–hazard ratio (HR) was 0.59 (95% confidence interval [CI] = 0.51 to 0.69). The pooled median-PFS was 17.8 months (95% CI = 16.5 to 19.3 months) for the combination vs 11.7 months (95% CI = 11.1 to 12.7 months) for EGFR-TKI as monotherapy. No statistically significant differences between the 2 treatment arms were observed in overall survival or objective response rate. The rate of grade equal or higher than 3 adverse events was statistically significantly higher in patients treated with EGFR-TKI plus an anti-angiogenic drug: the pooled-relative risk was 1.72 (95% CI = 1.43 to 2.06). Ten RCTs were included in the network meta-analysis. All 3 experimental treatments were associated with a statistically significant improvement in PFS compared with first-generation EGFR-TKIs. When compared to each other, none of the 3 experimental treatments were statistically significantly associated with larger PFS or lower rate of grade 3 or higher adverse events. Conclusion: Patients with EGFR-mutated non small-cell lung cancer derived clinically meaningful larger PFS benefit from the addition of an anti-angiogenic drug to a first-generation EGFR-TKI at the cost of an increase of toxicities.